Activation energy of thermal oxidation germanium oxide on germanium substrates - Halim, N.A.A.; Sahari, S.K.; Hamzah, A.A.; Majlis, B.Y.; Marini, Sawawi; Hasanah, L.; Kashif, M. (IEEE, 2018)
The activation energy of GeO2 was studied by determining the oxide thickness versus temperature from lower to higher oxidation temperature in the range between 450˚C and 600Ԩ. It was found that a linear relationship can be obtained between oxidation time and oxide thickness for the oxidation temperature between 450 and 575Ԩ while for the 600Ԩ , a linear relationship can be obtained for the shorter oxidation time. The rate of oxidation increased until 0.55 and abruptly decreased after increasing oxidation temperature to 600Ԩ which implies that the oxygen intermixing occurs during higher oxidation (600Ԩ) rather that diffusion mechanism that leads to the lower activation energy.